Subglacial water storage and drainage beneath the Fennoscandian and Barents Sea ice sheets. (1st December 2018) - Shackleton, Calvin; Patton, Henry; Hubbard, Alun; Winsborrow, Monica; Kingslake, Jonathan; Esteves, Mariana; Andreassen, Karin; Greenwood, Sarah L.
Abstract: Subglacial hydrology modulates how ice sheets flow, respond to climate, and deliver meltwater, sediment and nutrients to proglacial and marine environments. Here, we investigate the development of subglacial lakes and drainage networks beneath the Fennoscandian and Barents Sea ice sheets over the Late Weichselian. Utilizing an established coupled climate/ice flow model, we calculate high-resolution, spatio-temporal changes in subglacial hydraulic potential from ice sheet build-up (∼37 ka BP) to complete deglaciation (∼10 ka BP). Our analysis predicts up to 3500 potential subglacial lakes, the largest of which was 658 km 2, and over 70% of which had surface areas <10 km 2, comparable with subglacial lake-size distributions beneath the Antarctic Ice Sheet. Asynchronous evolution of the Fennoscandian Ice Sheet into the flatter relief of northeast Europe affected patterns of subglacial drainage, with up to 100 km 3 more water impounded within subglacial lakes during ice build-up compared to retreat. Furthermore, we observe frequent fill/drain cycles within clusters of subglacial lakes at the onset zones and margins of ice streams that would have affected their dynamics. Our results resonate with mapping of large subglacial channel networks indicative of high-discharge meltwater drainage through the Gulf of Bothnia and central Barents Sea. By tracking the migration of meltwater drainage outlets during deglaciation, we constrain locations most susceptible to focussed discharge, including the western continental shelf-break where subglacial sediment delivery led to the development of major trough-mouth fans. Maps of hydraulic potential minima that persist throughout the Late Weichselian reveal potential sites for preserved subglacial lake sediments, thereby defining useful targets for further field-investigation. Highlights: We present modelled subglacial water storage and drainage between 37–10 ka BP. Up to 3500 potential subglacial lakes predicted during LGM, storing >460 km 3 of water. Subglacial lake clusters are predicted with potential for fill/drain cycles and flood events. Persistent lakes over the glaciation define potential sites for preserved sediments. Catchment evolution and drainage outlet migration reveals subglacial discharge foci.